Abolishing Nuclear Weapons at a Time of Nuclear Revival: Prospects for the TPNW - Emmanuelle Maitre (Journal for Peace and Nuclear Disarmament, 2025)
Eight years after its adoption, the Treaty on the Prohibition of Nuclear Weapons (TPNW) remains a dynamic instrument that claims a place in the broader non-proliferation and disarmament regime. After three meetings of States Parties, it is pursuing its institutionalisation with working groups and reports on its different work streams. Moreover, its member states are committed to implement the plan of action adopted in Vienna in 2022, with a specific focus on positive obligations (victim assistance and environmental remediation), universalisation and verification. However, the change in the strategic environment and the constant opposition of nuclear weapon states and their allies to the Treaty limit what can be achieved in the short run and reduce the possibility of recognition of the TPNW as a full member of the architecture shaping the global nuclear order.